Bosnia and Herzegovina : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The current account deficit by the Central Bank of Bosnia and Herzegovina in recent years has fluctuated to about 20 percent of GDP. But official current account statistics suffer from several shortcomings. Possible sources of the savings required to achieve a fiscal position consistent with long-term fiscal sustainability is discussed. A theoretical model of the trade balance has been developed and used as the basis for estimating a quarterly regression model of Bosnia and Herzegovina's trade balance. Effective fiscal coordination is essential in Bosnia and Herzegovina.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy; International Agreements and Observance; International Organizations; Monetary Policy